The study of kinetics and thermodynamics of selected pharmaceuticals and personal care products on agriculture soil - Jodeh, Shehdeh (European Journal of Chemistry, 2012)
Pollution of the aquatic environment by human and veterinary waste pharmaceuticals is an increasing area of concern but little is known about their ecotoxicological effects on wildlife. In this study, three pharmaceuticals were selected (ibuprofen, amoxicillin and caffeine) as examples that are released in the environment. All of them are marketed in the Palestinian market (Pharmacies), private clinics and hospitals. The adsorption of the selected pharmaceuticals was examined by batch sorption experiments onto agriculture soil. Pharmaceuticals adsorption kinetics followed the pseudo-second-order adsorption model. Adsorption isotherms were best fitted by the Freundlich isotherm model. The “n” parameters were higher than 1 and the Kf values for all of them were less than 1. High removal rates of amoxicillin and ibuprofen were achieved in acidic media (pH = 1-4) and reached more than 88% Except for the caffeine increased at higher pH and reached more than 92%. The thermodynamics parameters showed that the adsorption process on soil was spontaneous and exothermic.